Why did the Soviet Union collapse? : understanding historical change - Strayer, Robert W. (Armonk, N.Y. : M.E. Sharpe, 1998)
Explores the collapse of the Soviet Union, placing it in the perspective of Russian, Soviet, and world history.
Includes bibliographical references and index.
Adult.
Adult
Keywords: Soviet Union -- History -- Philosophy; Soviet Union -- History -- 1985-1991.; Russia -- History -- Philosophy; Russia -- History -- 1953-1991.